Xử lý nước thải của quá trình sản xuất sữa bằng phương pháp hóa học - Triệu, Thị Nguyệt (Đại học quốc gia Hà Nội, 2017)
Waste water of Hanoi milk company was treated by oxidation method using CaOCl2 and CaO. The optimum conditions involving: pH, time and weight of CaOCl2 and CaO were studied. The obtained results were applied for the removal S^', organic compounds, smell and color in the milk waste water. The treated water is colorless and ordorless, S^" was completely removed, COD was reduced frorm 2120mg/l to 64 mg/1, which meet the requyrements of the waste water discharge standard.